Induction of tolerance in peripheral T cells with monoclonal antibodies. - Qin, S; Wise, M; Cobbold, S; Leong, L; Kong, Y; Parnes, JR; Waldmann, H (1990)
Our goal has been to develop ways to tolerize the mature immune system to any defined antigen. In this report we show that peripheral (post-thymic) T cells of mice can become tolerant to a range of antigens (human and rat immunoglobulins, and bone marrow and skin grafts that differ at multiple minor transplantation antigens). In the case of human gamma globulin (HGG), this required that the antigen be given under the cover of a short course of non-depleting anti-CD4 antibody, while for tolerance to skin and marrow grafts anti-CD8 antibody was also required. Tolerance to HGG could be reinforced by repeated injections of HGG, but was lost in the absence of any further exposure to antigen. This reversal of tolerance with time was due to new T cells being exported from the thymus, as it was not observed in tolerized, adult thymectomized mice. In contrast, tolerance to marrow and skin grafts was permanent, presumably because the established grafts acted as a continuous source of antigen to reinforce the tolerant state. Tolerance could not be broken by the infusion of unprimed spleen cells and in one example (tolerance to Mls-1a) there was clear evidence that specific peripheral T cells were anergic. We propose that anergic cells may themselves participate in reinforcing the tolerant state by competing at sites of antigen presentation.